Correlations between the Senior High School Grade 12 Students’ Perception of School Classroom Climate and Compliance to School Classroom Norms in a Private University in Manila, Philippines - Ahorro , Adrian Miguelle T.; David , Ma. Rafaella T.; Molina, Joaquin Maria V.; Pangilinan, Aimee Breanna Y.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This quantitative study aimed to determine the correlation between senior high school Grade 12 students’ perception of school climate and compliance with school classroom norms in a private university in Manila, Philippines. A sample of 249 Grade 12 respondents who were randomly selected answered the online self-administered questionnaire composed of modified scales to explore the two variables, with Cronbach tests exhibiting an acceptable level of internal consistency (perceptions school climate = 0.88, compliance of classroom norms = 0.86). The study found a positive perception of school climate (M = 4.19, SD = 0.40) and a very high level of classroom norm compliance (M = 3.40, SD = 0.32) among the respondents. The Pearson R test revealed a significant moderate positive correlation between their perception of school climate and their level of school classroom norm compliance and (r = 0.554, p < 0.001). This implies that their compliance or adherence to school classroom norms increases as their perception of school climate positively increases.